A CASE OF COMPOUND MAXILLARY ODONTOMA AND MANDIBULAR HYPODONTIA - Radka Cholakova; Ivan Chenchev; Svetla Jordanova; Diana Oncheva; Ljubomir Chenchev (Peytchinski Publishing, 2016)
Odontomas are formations which are still classified as benign tumors by the World Health Organization. They are lesions on any odontogenic tissue - enamel, cement and dentin, which are affected in different proportions and degree. We present a case of compound odontoma on upper jaw, on a 15 year-old girl, causing retention of a permanent canine tooth. After the extirpation 16 tooth-like structures were uncovered. The mandible was diagnosed with hypodontia of both 2nd premolars. Patient's history showed that there was a trauma in the area of the upper jaw at younger age. In this article we will present the clinical and radiographic examination, the stages of the complex surgical-orthodontic treatment and a discussion of the etiology of the diagnosis, complications and the treatment itself.